2018
DOI: 10.1007/s11695-018-3470-y
|View full text |Cite
|
Sign up to set email alerts
|

EUS-Guided Intragastric Injection of Botulinum Toxin A in the Preoperative Treatment of Super-Obese Patients: a Randomized Clinical Trial

Abstract: Intragastric injection of BTX-A does not appear to be an effective method of achieving preoperative weight loss in super-obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 46 publications
0
32
1
1
Order By: Relevance
“…EUS-guided interventions are increasingly advanced and are used for various therapeutic purposes (18) . EUS-guided coil combined with cyanoacrylate in order to reduce the risk of embolism in the treatment of gastric varices was first described in 2011 (7) .…”
Section: Discussionmentioning
confidence: 99%
“…EUS-guided interventions are increasingly advanced and are used for various therapeutic purposes (18) . EUS-guided coil combined with cyanoacrylate in order to reduce the risk of embolism in the treatment of gastric varices was first described in 2011 (7) .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most of the major adverse events were related to unrecognized intraoperative mucosal perforation. Some recent studies (7,37,38) found no difference in adverse events or efficacy after treatment with POEM vs Heller in patients treated with different previous therapies (dilation, Botox, and surgery) (4,7,21,(38)(39)(40)(41) . However, a separate prior study by Ren et al (42) showed a higher complication rate in POEM, perhaps related to the learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…Natomiast w innych badaniach klinicznych nie obserwowano korzystnego wpływu toksyny botulinowej na masę ciała i czas opróżniania żołądka [27,28]. Najnowsze badania wskazują również na brak jej skuteczności w zmniejszaniu wagi przed operacjami u osób bardzo otyłych [29]. Te sprzeczne doniesienia mogą wynikać z różnic dotyczących miejsc podania toksyny, zastosowanych dawek oraz kryteriów doboru pacjentów.…”
Section: Nowe Kierunki Zastosowania Toksyny Botulinowejunclassified